A true development round? A review of Joseph E. Stiglitz and Andrew Charlton's Fair trade for all : how trade can promote development - Lawrence, Robert Z. (2007)
Elaborates on three issues that are central to the book. Discusses the problems that developing country heterogeneity presents for prescriptions for a true development round. Explores the implications of trying to ensure that in addition to promoting development, the agreement is fair. Considers one's ability to forecast the effects of trade agreements.